OF CERTAIN COMPOUNDS WITH ONOMASTIC COMPONENTS IN UZBEK AND ENGLISH COMPARATIVE ANALYSIS - Matyakubov Khakimboy Khamidjanovich (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article provides a linguistically comparative analysis of onomastic companent consonants in Uzbek and English. The existing similarities and differences between onomastic component compounds in Uzbek and English are highlighted on the basis of comparative analysis, showing the influence of National thinking, historical experience and Culture on the naming process.